KNOWLEDGE, RISK PERCEPTION, AND MEDICATION DISPOSAL PRACTICES AMONG HEALTH SCIENCES STUDENTS - José Victor Casas dos Santos; Thiago Ponce de Leão Monteiro; Daniel de Almeida Campos; Renato Melo da Silva; Gabriel de Andrade Bezerra; Igor Venturim Ferreira; Sofia Cardoso de Oliveira Rezende; Márcio Luís Lombardi Martinez (Artefactum - revista de estudos interdisciplinares, 2026)
The study aimed to characterize knowledge, perception of environmental and health risks, and medication disposal practices among health sciences students, comparing results according to academic program and assessing associations among these characteristics. An observational, cross-sectional, descriptive-analytical study was conducted with 204 students from Physical Education (n=10), Nursing (n=35), Medicine (n=130), and Dentistry (n=29) at a higher education institution in Amazonas, Brazil. Data were collected using a structured questionnaire addressing household medication storage, knowledge of regulatory provisions, risk perception, and disposal practices. Categorical variables were described using absolute and relative frequencies, and associations with academic program were assessed using Pearson’s chi-square test, with a 5% significance level. Household medication storage was common among students. Knowledge of RDC No. 222/2018 and the National Solid Waste Policy was low, whereas risk perception was high. Correct medication disposal practices ranged from 20.0% to 50.0%. No significant associations were observed between academic program and correct disposal practices (χ²=5.468; p=0.141), knowledge of RDC No. 222/2018 (p=0.314), or knowledge of the National Solid Waste Policy (p=0.728). A significant association was observed between academic program and risk perception (χ²=8.094; p=0.044). The findings reveal a gap between risk perception, regulatory knowledge, and actual disposal practices, highlighting the need to integrate environmental education, reverse logistics, and information on medication take-back points into the education of health sciences students.